Faktor-Faktor yang Berhubungan dengan Kejadian Diare pada Balita di Puskesmas Bulu Lor Kota Semarang - Nurfita, Desi (Universitas Ahmad Dahlan, 2017)
Background: Diarrhea is still being a global health problem especially in developing countries. In Indonesia diarrhea is still one of the major public health problems. It is often affects infants and toddlers, if not be treatment further will lead to dehydration and resulting death. Many factors cause diarrhea in infants, either directly or indirectly. Method: This study was an observational analytic using cross sectional design, there were 84 respondents of mothers who have children under five who are live in surround the work area of Puskesmas Bulu Lor Kota Semarang. The data was collected using a questionnaire. Primary data were obtained from direct interviews to re respondents. Data analysis was done by using Chi-Square test (univariat and bivariate). Results: Based on statistic test, this study found that factors related to diarrhea at Puskesmas Bulu Lor Kota Semarang were Exclusive Breast Milk (p-value=0.018), existence of Flies (p-value=0.043), and restroom ownership (p-value=0.031). While the factors that are not related to the incidence of diarrhea in Puskesmas Bulu Lor Kota Semarang are knowledge (p-value=0.705) and clean water (p-value=1.000). Conclusion: The result of this study can be concluded that there is a relationship between exclusive breast milk, the existence of flies, and the ownership of restroom with the incidence of diarrhea at the Puskesmas Bulu Lor Kota Semarang.